2017
DOI: 10.1130/g38459.1
|View full text |Cite
|
Sign up to set email alerts
|

Barrier island migration dominates ecogeomorphic feedbacks and drives salt marsh loss along the Virginia Atlantic Coast, USA

Abstract: *-note that Table DR1 only contains data sources used to map marsh and open water areas. We direct the reader to Himmelstoss et al. (2010) for a list of the sources used in that study to compile the shoreline dataset (of which we used the "Delmarva south" portion in this study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 33 publications
5
52
0
Order By: Relevance
“…Increased variance in rates of marsh–upland conversion identified here is consistent with a shift in the system toward increasing rates of landward barrier island migration, a change that has been recognized in other recent work (Deaton et al, ). At the same time, the expansion of woody vegetation is creating new ecological scenarios (e.g., monotypic thickets that dominate the landscape) that have not been present historically.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increased variance in rates of marsh–upland conversion identified here is consistent with a shift in the system toward increasing rates of landward barrier island migration, a change that has been recognized in other recent work (Deaton et al, ). At the same time, the expansion of woody vegetation is creating new ecological scenarios (e.g., monotypic thickets that dominate the landscape) that have not been present historically.…”
Section: Discussionsupporting
confidence: 89%
“…Understanding connectivity of sediment via the transport of sediment across multiple habitat types on barrier islands is essential in improving future predictions of coastal response to climate change, especially given the various drivers that can alter the system. Recently, it was demonstrated that connection between the upland and backbarrier environment plays as an important in the maintenance of barrier island–marsh systems (Walters et al, ), and is an innovative framework for assessing barrier system stability over the past 150 years (Deaton et al, ) and sediment mobility during storms (Houser, Hapke, & Hamilton, ). Here, we fill a knowledge gap by extending the framework of coupled ecosystems identified in previous work by considering how upland vegetation affects the conversion of backbarrier marsh into barrier island upland along the VBI.…”
Section: Introductionmentioning
confidence: 99%
“…Deaton et al () show that under some circumstances the sediment input and basin geometry do not allow a back‐barrier marsh to prograde as quickly as the associated barrier island is migrating, ultimately resulting in loss of the back‐barrier marsh due to burial of the marsh by the island. However, given the interdependencies between barrier islands and back‐barrier marshes, increased resilience for back‐barrier marshes, even if only temporary, has important implications for barrier islands.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we quantify dispersal in a spatially disconnected system, where long-distance events contribute to woody encroachment. As islands become reduced in size, inter-island distance is increasing , Deaton et al 2017.…”
Section: Introductionmentioning
confidence: 99%